Smoking Among Pregnant Women in Outpatient Treatment for Opioid Dependence: A Qualitative Inquiry - Fallin, Amanda (Nicotine Tob Res, 2016)
INTRODUCTION: Smoking during pregnancy is a major public health issue, contributing to adverse health outcomes. The vast majority of women with substance use disorders smoke during the perinatal period. Medication Assisted Treatment (MAT) is the standard of care for women using opioids during pregnancy. The majority of women engaged in MAT (88%–95%) report smoking. The purposes of this study were to describe: (1) facilitators and barriers to engaging in tobacco treatment among pregnant, opioid dependent women receiving MAT; and (2) strategies to tailor tobacco treatment interventions with this population. METHODS: Two semi-structured focus groups lasting approximately 45 minutes each were conducted with 22 women engaged in MAT. Focus groups were recorded, transcribed and analyzed in MAXQDA using content analysis. RESULTS: Participants reported: (1) desire to quit smoking for themselves and their children; (2) aversion to smoking; (3) a turning point in their lives from being pregnant and entering MAT; (4) nicotine dependence; (5) smoking as a way to cope with stress; (6) coping with dual dependencies; (7) past experiences with stopping smoking due to smoking restrictions; (8) perceived lack of success with nicotine replacement therapy or other tobacco treatment medications; and (9) the need for intensive environmental support for quit attempts. CONCLUSIONS: Participants were motivated to quit smoking, but faced multiple complex barriers. Integrating tobacco treatment into the psychosocial services offered in conjunction with MAT would allow a healthcare provider to offer tailored tobacco treatment in a supportive environment. IMPLICATIONS: Results of this qualitative study include facilitators and barriers to engaging in tobacco treatment among pregnant, opioid dependent women receiving MAT, as well as strategies to tailor tobacco treatment interventions for this population. In-depth knowledge of the complex barriers facing this patient population can be used to inform tailored tobacco treatment services that can be integrated into clinics providing MAT.